Perancangan Sistem Kontrol Lampu Berbasis Mikrokontroler Arduino Uno R3 dengan Sensor Suara (Studi Kasus : PT. Kopi Oey Cabang Telkom) - Ronni Sahat Hutabarat; Nur Nawaningtyas (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to design and evaluate an automatic light control system based on the Arduino Uno R3 microcontroller integrated with a sound sensor, implemented at PT. Kopi Oey, Telkom Branch. The development of this system was motivated by the growing need for automation in the food and beverage (F&B) industry, aiming to improve energy efficiency, reduce operational errors, and support sustainable business operations through technology- based innovation. Materials and methods. The system was designed to respond to sound input—such as hand claps—detected by a sound sensor connected to the Arduino Uno R3. The microcontroller processes the input and triggers a relay module to turn lights on or off automatically. The system was tested in a real working environment to evaluate functionality and responsiveness. Usability was assessed through a standardized questionnaire measuring five aspects: Learnability, Efficiency, Memorability, Errors, and Satisfaction. Results. All usability aspects scored above 4.4 on a 5-point scale, with Efficiency (4.56) and Memorability (4.55) being the highest, indicating excellent usability and performance. Conclusions. The voice-activated lighting system proved effective, user-friendly, and energy-efficient, offering a practical automation solution for commercial environments and paving the way for future Internet of Things (IoT) integration.